Publication Trend of Open Access Journalis in Indonesia - Heriyanto, Heriyanto; Al Fauzan, Muhammad (Universitas Airlangga, 2022)
The purpose of this research is to determine the publication trend of open access journals in Indonesia. A systematic review was used as the research method in this study. The focus of this study is to identify the themes that are most frequently discussed and discovered in studies on open access journals in Indonesia. According to the findings of this study, the most frequently discussed research themes were those concerning journal governance, marketing strategies, user perspectives, and matrices. Although several themes were discovered, the most frequently discussed theme was journal governance, specifically the challenges and problems faced by journal managers. Financing issues, journal quality, and piracy are among the challenges and issues discussed. This is due to the state of open access journals, which are still evolving in response to technological advancements.